2021
DOI: 10.1016/j.ajic.2020.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 222-nm ultraviolet light on disinfecting SARS-CoV-2 surface contamination

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has emerged as a serious threat to human health worldwide. Efficient disinfection of surfaces contaminated with SARS-CoV-2 may help prevent its spread. This study aimed to investigate the in vitro efficacy of 222-nm far-ultraviolet light (UVC) on the disinfection of SARS-CoV-2 surface contamination. Methods: We investigated the titer of SARS-CoV-2 after UV irradiation (0.1 mW/cm 2) at 222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
214
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 228 publications
(236 citation statements)
references
References 21 publications
(45 reference statements)
6
214
1
2
Order By: Relevance
“…In the current global pandemic of SARS-CoV-2, means to inactivate viruses and prevent infections must be taken. DUV irradiation is one powerful and effective way to combat various microorganisms including SARS-CoV-2 and related coronaviruses [10][11][12][13][14][15][16][17]. However, in order to establish commonly and widely usable inactivation apparatuses/techniques using DUV, reliable quanti ed data that can serve as a solid standard for their development are required; the length of the DUV irradiation periods, which wavelength, and what doses of DUV are needed for SARS-CoV-2 inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current global pandemic of SARS-CoV-2, means to inactivate viruses and prevent infections must be taken. DUV irradiation is one powerful and effective way to combat various microorganisms including SARS-CoV-2 and related coronaviruses [10][11][12][13][14][15][16][17]. However, in order to establish commonly and widely usable inactivation apparatuses/techniques using DUV, reliable quanti ed data that can serve as a solid standard for their development are required; the length of the DUV irradiation periods, which wavelength, and what doses of DUV are needed for SARS-CoV-2 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…While the biological effects of DUV light have been widely proven across different types of viruses [14,[16][17][18][27][28][29][30][31], the precise mechanism by which the DUV light inactivates viruses remains to be elucidated [18]. Several studies reported that virus inactivation by DUV irradiation is primarily caused by the photochemical reactions of nucleic acids [18,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent reports have shown the effectiveness of ultraviolet light (UV) irradiation for inactivating SARS-CoV-2 [ [4] , [5] , [6] ]. The effectiveness of 222 nm UVC light for disinfecting surfaces contaminated with SARS-CoV-2 has been reported [ 7 ]. In this previous study, the 222 nm UVC-emitting device, Care222™(Ushio Inc., Tokyo, Japan; Dimensions: 205 mm x 150 mm x 50 mm) was used and the effect of 0.1 mW/cm 2 222 nm UVC with multiple irradiation times on surfaces contaminated with SARS-CoV-2 was investigated [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of 222 nm UVC light for disinfecting surfaces contaminated with SARS-CoV-2 has been reported [ 7 ]. In this previous study, the 222 nm UVC-emitting device, Care222™(Ushio Inc., Tokyo, Japan; Dimensions: 205 mm x 150 mm x 50 mm) was used and the effect of 0.1 mW/cm 2 222 nm UVC with multiple irradiation times on surfaces contaminated with SARS-CoV-2 was investigated [ 7 ]. When Care222™ was installed on the ceiling or wall, the UV irradiance of distant areas such as desks and floors was lower than that of a previous study setting [ 7 ].…”
Section: Introductionmentioning
confidence: 99%